Assessing Soil Contamination for Sustainable Waste Management: A Case Study of Municipal and Industrial Waste Impact in Haryana - Seema, Seema (Journal of Neonatal Surgery, 2025)
This study explores the critical interrelationship between soil chemistry and effective waste management practices in Haryana. The state faces severe challenges related to the management of municipal and industrial waste as urbanization and industrial activities accelerate leading to significant soil contamination. The study highlights the improper waste disposal practices that result in elevated concentrations of heavy metals, persistent organic pollutants, and other hazardous substances that alter key soil properties such as pH, electrical conductivity, and organic carbon content. The implications of these changes threaten soil fertility, disrupt microbial activity, and increase the risk of bioaccumulation, thereby jeopardizing agricultural sustainability and groundwater quality. The study emphasizes the importance of understanding soil chemistry in assessing contamination risks and developing sustainable waste management strategies. The study discusses about how soil components interact with contaminants by examining the behavior, transformation, and mobility of pollutants within soil ecosystems that influences their availability in soil and potential harm to human health and the environment. The study has highlighted the gaps in waste management infrastructure, particularly in leachate control and hazardous waste regulation, while also assessing advanced remediation strategies such as chemical stabilization, bioremediation, and phytoremediation. Sustainable soil recovery requires integrated approaches combining regulatory enforcement, periodic monitoring and adaptive remediation methods. The study emphasizes the need for scientific waste management policies to mitigate soil degradation, protect agricultural productivity, and ensure long-term ecological resilience in Haryana.